pH-changes during intracoronal bleaching: An in vivo study - Barcellos, Daphne Câmara [UNESP]; Borges, Alessandra Buhler [UNESP]; Silva, Regina Célia dos Santos Pinto [UNESP]; Ribeiro, Luciana Maria [UNESP]; Pucci, Cesar Rogério [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Jaypee Brothers Medical Publishing, 2011)
Objectives: This study aimed to measure pH changes during 14 days intracoronal bleaching with hydrogen peroxide/sodium perborate and carbamide peroxide/sodium perborate. Materials and methods: Twenty patients presenting endodontically treated central maxillary incisors with color alterations were divided in two groups (n = 10): Group CP + SP: 37% carbamide peroxide + sodium perborate paste; Group HP + SP: 30% hydrogen peroxide + sodium perborate paste. The pH values were measured using a digital microprocessor at different times: Baseline, 2, 7 and 14 days. Data were analyzed with two-way ANOVA followed by Tukey's test (α = 0.05). Results: ANOVA showed p < 0.00 which indicated significant difference between the groups. The mean values (± sd) and the results of the Tukey's test were: HP + SP/14 days-7.98 (±0.58)a; HP + SP/7 days-8.59 (±0.18)b; HP + SP/2 days-8.83 (±0.32)bc; HP + SP/Baseline-8.83 (±0.01)bc; CP + SP/Baseline-8.89 (±0.01)bc; CP + SP/14 days-9.11 (±0.58)cd; CP + SP/7 days-9.54 (±0.16)de; CP + SP/2 days-9.66 (±0.08) de. The group HP + SP resulted in significantly lower pH values compared with group CP + SP. Conclusion: It can be concluded that both associations showed alkaline pH values; however, there was significant reduction in the pH values of the 30% hydrogen peroxide associated with sodium perborate after 14 days. Clinical Significance: The association of hydrogen peroxide and carbamide peroxide with sodium perborate paste presented alkaline characteristics during the 14-day evaluated period. Thus, regarding pH changes, both associations can be considered safe as intracoronal bleaching agents.
Keywords: Bleaching agents; Intracoronal; Peroxides; pH; boric acid; drug derivative; hydrogen peroxide; perborate sodium; peroxide; tooth bleaching agent; urea; urea peroxide; adolescent; adult; analysis of variance; chemistry; clinical trial; controlled clinical trial; controlled study; dental procedure; drug combination; human; methodology; middle aged; nonparametric test; tooth pulp disease; Adolescent; Adult; Analysis of Variance; Borates; Drug Combinations; Humans; Hydrogen Peroxide; Hydrogen-Ion Concentration; Middle Aged; Statistics, Nonparametric; Tooth Bleaching; Tooth Bleaching Agents; Tooth, Nonvital; Urea; Young Adult